Virksomhedsledelse og den autoritære stat. Knud Højgaard 1878-1968 - Lund, Joachim (Historisk Tidsskrift, 2013)
Business Management and the Authoritarian State Knud Højgaard 1878-1968Knud Højgaard (1878-1968), Danish engineer and businessman, is already becoming known to posterity for having lent his name to the so-called Højgaard Circle that in November 1940, during the first year of the German occupation, approached King Christian X with a request to replace Prime Minister Stauning’s national coalition government with a council of experts unfettered by parliamentary concerns. It would seem the Circle had already influenced the decision made earlier that year, in July, to replace the foreign minister, Peter Munch, with Eric Scavenius and to appoint a businessman, Gunnar Larsen, as Minister of Public Works. But there is a tendency to overlook the fact that Højgaard none the less was also one of Denmark’s most successful and influential businessmen of the twentieth century. The present study combines business history with the history of political culture and argues that Højgaard’s political and strong nationalist commitment must be understood in the context of his career as an engineer and business leader. During a period characterized by an unprecedented degree of state economic intervention, he developed his own critique of parliamentary democracy on the basis of a classic conservative conception of the role of the state in society. Management by definition required an authoritarian foundation, but as the study shows, criticism of the parliamentary system thrived in particularly fertile ground among Danish businessmen with an engineering background. These men were also sensitive to the technocratic movement of the inter-war years, when it established itself as an ideological alternative to parliamentary democracy, fostering protagonists also in Denmark. The broader antiparliamentary currents of the times were reflected in Denmark in publications such as Gads Danske Magasin, which cultivated outstanding contemporary figures, among them Knud Højgaard. Højgaard’s prestige was steadily increasing within the 1930s network of Danish business leaders, and by 1937 he was beginning to surround himself with politically like-minded colleagues, initially to influence the government's defence policy. The 1940 Højgaard Circle can be traced back to these groups. Højgaard's numerous foreign business enterprises brought him closer to international political developments than most Danish business leaders, who were typically focused on domestic affairs. Højgaard and Schultz Ltd., the engineering and construction company, co-founded by Knud Højgaard shortly after World War I, expanded in the 1920s especially in Eastern European countries, then expanded further in the 1930s, particularly in Portugal. Højgaard’s positive experience in dealing locally with authoritarian regimes evoked a deeper interest in them and eventually turned him into an advocate; in his view, these political systems had replaced parliamentary paralysis with sober policies and regard for the common good. Political mass movements were not to his taste, but as he saw it, there was something to be learned from Salazar’s discrete dictatorship in Portugal and the Vichy regime’s national revolution in France. Højgaard’s critical attitude towards democracy and his admiration of Salazar's rule throw light on his motives in attacking the parliamentary government in Denmark in 1940. From Højgaard’s perspective it was not simply Stauning’s government, specifically, that blocked an acceptable relationship with the Germans, but the parliamentary system in general. What he failed to see was that a Danish counterpart to the Vichy regime would probably have entailed greater danger to the survival of the Danish national state, for such a Danish government of technocrats and businessmen, »liberated« from political parties and voters, would also have deprived itself of its last bulwark against increasing German pressures, as happened in Vichy 1940-42. Translated by Michael Wolfe